Explorations of the impacts on a hydrogen fuelled opposed rotary piston engine performance by ignition timing under part load conditions. (23rd March 2021) - Gao, Jianbing; Tian, Guohong; Ma, Chaochen; Huang, Liyong; Xing, Shikai
Abstract: High power density of opposed rotary piston (ORP) engines provides a possibility for the applications to hybrid vehicles. Under real driving conditions, internal combustion engines as the power sources of hybrid vehicles run under part load conditions in majorities of operation time. Hydrogen applications in internal combustion engines will promote zero-carbon travel, contributing to alleviating global warming. In this investigation, 3D numerical simulations were conducted to explore the performance of an ORP engine fuelled with hydrogen under part load and various ignition timing conditions. The results indicated that peak in-cylinder pressure and corresponding crank angle (CA) changed slightly within the early ignition range of −20.85º CA −14.23º CA; peak in-cylinder pressure was decreased significantly by late ignition. Heat release rates were more sensitive to late ignition than early ignition. Start of combustion, combustion phase, and combustion durations presented minor impacts by early ignition and engine loads. Ignition timing of −20.85º CA −11.06º CA showed limited impacts on indicated mean effective pressure and indicated power over individual intake manifold pressure. Indicated thermal efficiency was around 40% for the ignition timing of −20.85º CA −11.06º CA over the intake manifold pressure of 0.8 bar; indicated thermal efficiency drop caused by ignition timing of −8.33º CA was higher than 7% compared with optimal conditions. Heat loss by cylinder walls in proportions of fuel energy was lower than 25%, 20%, 18% for the intake manifold pressure of 0.4 bar, 0.6 bar, 0.8 bar respectively. Energy loss by the exhaust was higher than 41% for all the scenarios, with the maximum value being approximately 57%. Nitrogen oxides (NO x ) emission factors were higher than 11 g (kW h) −1, and they were increased significantly by early ignition. Graphical abstract: Image 1 Highlights: Spark plugs layout led to special combustion characteristics and engine performance. In-cylinder pressure evolutions were dependent less on early ignition timing. Combustion durations presented the smallest value over ignition timing of −11.06º CA. Exhaust energy accounted for higher than 41% of the total fuel chemical energy. NO x were higher than 11 g (kW h) −1, being increased greatly by early ignition.